Alteration Characteristics and Precious Metal Availability in Gunung Gembes & Surroundings, Jeruk Village, Pacitan Regency, East Java Province - Radhitya Adzan Hidayah; I Gusti Ngurah Adi Prasetiya; Nurul Adzan Dzakiya (Politeknik Negeri Batam, 2022)
The research area is located in the area of Mount Gembes, Jeruk Village in Pacitan (East Java). This study aims to determine the characteristic and temperature in the formation of alteration which refers to petrography with the help of samples taken in the study area. The petrographic observations carried out were thin section observations which were then analyzed for the mineral content contained in the sample rock. After knowing the minerals contained in the sample rock, it is then entered into the mineral formation temperature diagram (White & Hedenquist, 1995). The method used in this study includes primary data in the form of geological observations such as lithology, geological structure geomorphology, environmental geology and alteration observations and combined with secondary data. Alteration observations in this study were carried out descriptively (megascopic) and subjective (microscopic). The geomorphic unit that works is of volcanic origin, with high hilly sub-units of porphyry dacite intrusion (volcanic neck). Geological structures that develop in the study area are faults, namely the left horizontal fault of Jeruk 1, the left horizontal fault of Jeruk 2 and the interpretation of the oranges right horizontal fault. Geological resources or sources found in the research area are mineral potential resources that are economical, and negative sources are in the form of mass movement of debris flow type. The Zonation and the type of alteration that developed in the research area are the clay alteration zone and silicification. The clay zone is formed at a temperature >100⁰C-220⁰C with a pH of 3-5 and a silicification zone is formed at a temperature>100⁰C-300⁰C with a pH <2 which is directly controlled by the faults found in the study site.